Semiotics of Old Age in Polish Neo-Latin Poetry. Samboritanus, Cochanovius, Treter, Sarbievius, Ines - Buszewicz, Elwira (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The main aim of this paper is to analyze several early-modern Neo-Latin poems written by Polish authors; the poems deal (in different ways) with old age. The poets undertake a kind of intertextual game with the reader, applying various stereotypes and clichés. On can speak about a “semiotic landscape” of old age. The authors taken into consideration are Jan Kochanowski, Grzegorz of Sambor, Thomas Treter (16th century) and Maciej Kazimierz Sarbiewski, Albert Ines (17th century).